2022
DOI: 10.1093/nar/gkac656
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of anti-CRISPR operon repression by Aca10

Abstract: CRISPR-Cas systems are bacterial defense systems for fighting against invaders such as bacteriophages and mobile genetic elements. To escape destruction by these bacterial immune systems, phages have co-evolved multiple anti-CRISPR (Acr) proteins, which inhibit CRISPR-Cas function. Many acr genes form an operon with genes encoding transcriptional regulators, called anti-CRISPR-associated (Aca) proteins. Aca10 is the most recently discovered Aca family that is encoded within an operon containing acrIC7 and acrI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Although various Acrs inhibit CRISPR-Cas activity in monomeric form, previous studies have shown that the dimeric form of Acrs is often critical for their activity ( 29 , 53 , 54 ). Similarly, some Aca proteins have been shown to function as dimers ( 31 , 33 , 55 ). Given the possible dimeric form of AcrIF24 as judged by our SEC experiment, we used multi-angle light scattering (MALS) to confirm the stoichiometry by determining the absolute molecular mass of AcrIF24 in solution.…”
Section: Resultsmentioning
confidence: 99%
“…Although various Acrs inhibit CRISPR-Cas activity in monomeric form, previous studies have shown that the dimeric form of Acrs is often critical for their activity ( 29 , 53 , 54 ). Similarly, some Aca proteins have been shown to function as dimers ( 31 , 33 , 55 ). Given the possible dimeric form of AcrIF24 as judged by our SEC experiment, we used multi-angle light scattering (MALS) to confirm the stoichiometry by determining the absolute molecular mass of AcrIF24 in solution.…”
Section: Resultsmentioning
confidence: 99%
“…To generate the VEGF 165 /aptamer complexes, we utilized the HDOCK docking program [40,41] by utilizing all combinations of the conformations described in the previous section. In fact, HDOCK has been extensively adopted recently to analyze protein-RNA and protein-DNA interactions [42][43][44], and it has shown excellent performance [45] in the community-wide Critical Assessment of Prediction of Interactions (CAPRI) [46]. To further verify its applicability to our systems, we conducted a docking experiment between VEGF 121 and domains 2 and 3 (D23) of VEGFR-2 with it.…”
Section: Ensemble Docking Of Aptamers With Vegf 165mentioning
confidence: 99%
“…For instance, AcrIC9 from Rhodobacter capsulatus is the most recently identified AcrIC family member that inhibits the type IC CRISPR-Cas system (Gussow et al, 2020). The expression of many acr genes is controlled by putative transcriptional regulators called anti-CRISPR-associated proteins (Acas) (Birkholz et al, 2019;Stanley et al, 2019), which are thus indirect regulators of CRISPR-Cas systems (Lee et al, 2022;Malone et al, 2021). Because Acrs and Acas regulate the activity of CRISPR-Cas systems, they are considered to be promising tools for controlling gene editing using CRISPR-Cas (Marino et al, 2020).…”
Section: Introductionmentioning
confidence: 99%